Physical and Functional Interaction of Mitochondrial Single-Stranded DNA-Binding Protein and the Catalytic Subunit of DNA Polymerase Gamma - Ciesielski, Grzegorz L.; Kim, Shalom; de Bovi Pontes, Carolina; Kaguni, Laurie S. (Frontiers in Genetics, 2021)
The maintenance of the mitochondrial genome depends on a suite of nucleus-encoded proteins, among which the catalytic subunit of the mitochondrial replicative DNA polymerase, Pol γα, plays a pivotal role. Mutations in the Pol γα-encoding gene, POLG, are a major cause of human mitochondrial disorders. Here we present a study of direct and functional interactions of Pol γα with the mitochondrial single-stranded DNA-binding protein (mtSSB). mtSSB coordinates the activity of the enzymes at the DNA replication fork. However, the mechanism of this functional relationship is elusive, and no direct interactions between the replicative factors have been identified to date. This contrasts strikingly with the extensive interactomes of SSB proteins identified in other homologous replication systems. Here we show for the first time that mtSSB binds Pol γα directly, in a DNA-independent manner. This interaction is strengthened in the absence of the loop 2.3 structure in mtSSB, and is abolished upon preincubation with Pol γβ. Together, our findings suggest that the interaction between mtSSB and Pol γ involves a balance between attractive and repulsive affinities, which have distinct effects on DNA synthesis and exonucleolysis.